Öğretmenlerin sahip oldukları değerlerin ve özgeci davranışlarının mesleki benlik saygısı açısından incelenmesi - (:unkn) unknown (My University, 2012)
Bu araştırmanın amacı, öğretmenlerin sahip oldukları değerler ile özgeci davranışlarının mesleki benlik saygısı açısından incelenmesidir. Araştırma, ilişkisel tarama modelindedir. Araştırma veri bağlamında nicel bir paradigmaya sahiptir. Araştırmada veri toplama aracı olarak Schwartz (1992) tarafından geliştirilen Değerler Listesi ve Yavuzer, İşmen-Gazioğlu ve Yıldız (2006), tarafından geliştirilen Öğretmen Özgeciliği Ölçeği ve Arıcak (1999) tarafından geliştirilen mesleki benlik saygısı ölçeği kullanılmıştır. Araştırmada veriler toplandıktan sonra, araştırmanın amacı doğrultusunda her iki ölçeğe ait alt boyutlardan elde edilen puanlara göre Pearson Çarpım Monetler Katsayıları ve Regresyon analizi yapılmıştır. Araştırma sonucunda elde edilen bulgulara bakıldığında, öğretmenlerin sahip oldukları değerler ve özgeci davranışları ile mesleki benlik saygıları arasında ilişkinin var olduğu görülmüştür.

Introduction This research is the examination of the values teachers have and their altruist behaviors in terms of the vocational self-esteem respect. The teacher should bring up his students as the individuals having academic success, social skills, positive, trustful and sound behaviors, contributing morally and having responsibility to their peer group, family, school, society, and having value, job habits and basic skills. Today, the view on that teachers not being in a situation as a passive person only giving information, but them to be modeled with their values and believes should be common. It is possible for students to get some acqusition and shape them apart from their living quarters as well. In this context, this research is the research conducted in terms of value, altrusm and vocational self-esteem respect which should be in the teaching profession. Purpose In this research, the value the teachers have and the examination of their altruist bahaviors in terms of the vocational self-esteem respect is purposed. In this context, this research was conducted for the purpose of the examination of the relation between the values the teachers have and the altruist behaviors and to determine the values teachers have and their altruist behaviors’ power to explain the teachers’ vocational self-esteem respect level. Method Much of social research in general, and educational research more particularly, is concerned at establishing interrelationships among variables (Cohen, Manion & Morrison, 2000). Such kinds of researches which are conducted for the purpose of determining the relation between the two or more variables and getting clues related to the reason and conclusion are the correlational researches. (Büyüköztürk vd., 2008) Correlational techniques are generally intended to answer three questions about the variables or two sets of data. First, ‘Is there a relationship between the two variables (or sets of data)?’ If the answer to this question is ‘yes’, then two other questions follow: ‘What is the direction of the relationship?’ and ‘What is the magnitude?’ (Cohen, Manion & Morrison, 2000). The working scope of the research consists of the teachers who are in the province, Konya. Hoewever, the working group of the research consist of 422 teachers, 275 of whom are men, whereas 147 of whom are women. The research has a quantitative paradigm in the data context. In the research, the values list developed by Schwartz and the teacher altruist scale developed by Yavuzer, İşmen-Gazioğlu and Yıldız (2006) and vocational self-esteem respect scale developed by Arıcak (1999) were used as data collection tool. Scale tools were applied to the teachers working in Konya. It was base to be volunteer and its being reachable. After the applications were completed, data collection was included in to the SPSS 15 (2006) programme. All of the analyses were conducted in the SPSS 16 for Windows (2006). However, while testing the power of examination of the vocational self-esteem respect level of the teachers, multiple regression analysis was conducted. Findings The relation is seen between hedonism and excitement sub dimensions of the points of teachers’ vocational self-esteem respect scale and the values scale. The relation was not found between the power, success and self-esteem respect sub dimensions of the values scale. The relation is seen between the points of the teachers’ vocational self esteem respect scale and the sharing the social responsibilty sub dimensions of altrusim scale. The relation was not found between the sub dimensions of helpfulness in current conditions, helpfulness in urgent conditions and donation. According to the variables of altrusim and values, results of the regression analysis related to the examination of the points of vocational self esteem respect were stated in the table above. There is a significant relation between the sub dimensions of values and altrusim scales and points of teachers’ vocational self-esteem respect together.( R= 0.20, R= 0.40, P <.05). Subdimensions of the values scale and subdimensions of altrusim scale together explain 40 % of the vocational self- esteem respect of the teachers. Discussions & Conclusions Discussion process was followed in the light of the findings obtained from the examination of the research titled as the ‘examination of the values the teachers have and their altrusim behaviors in terms of the vocational self esteem respect’. Seeing the findings obtained from the research, it was determined that there was the relation between the hedonism and stimulation sub dimensions of the teachers’ vocational self-esteem respect and values scale and the relation was not found between the sub dimensions of power, success, self-control, universality, helpfulness, traditionality, adaptation and confidence. Kunes-Connell (1991), state that person’s skill of realizing the roles expected from themselves and competence in the interpersonel relations shape his vocational self -esteem respect. In this respect, we can say that some terms such as ‘to be competence’, ‘to be successful’ which we think that their affecting the self -esteem affect the vocational self -esteem respect as well. In another finding obtained from the research, the relation is seen between the sharing of social responsibilty sub dimensions of vocational self -esteem respect and altrusim scale. The relation was not found between the sub dimensions of helpfulness in current conditions, helpfulness in urgent conditions and donation. The research finding realized by İşmen and Yıldız (2005) support this. Candidate teachers having altruist behaviors at higher levels state that they have more positive attitude than the ones being altruist at lower levels. According to the findings realized by Onatır (2008), as the subdimension points of altrusim scale at current conditions increase, success, hedoism, stimulation, self-control, universality, helpfulness, adaptation, and confidence sub dimension points of values scale increase as well. Sub dimensions of value scale and sub dimensions of altrusim scale together explain the 40 % of the vocational self -esteem respect. However, in the research finding realized by Yılmaz and Dilmaç (2011), teachers’ working satisfaction explain the human values significantly. Seeing the results of analysis in terms of the dimensions of the human values, adaptation and traditionality of the human values explain the teachers’ working satisfaction significantly. Even though it is not related to the research finding directly, the result obtained support the research finding at least partially in terms of both working group and values scale being the same among the scales. However, in a research conducted by Dilmaç (2009), seeing the findings obtained, it is seen that the vocational competence perception of teacher is related to other three sub dimensions (helpfulness in current conditions, sharing social responsibilty, helpfulness in urgent conditions) except for the sub dimension, donation, among the sub dimensions of teacher altrusim scale. This finding supports the finding obtained from the research even if it is indirectly. According to Brief (1998), working people can be satisfied only when they get the final and tool values. If the work is contrary to the values they have, they may not be satisfied with their job. Values determine the quality of the vocation people will select and so their philosophy as well. According to Super and Bohn (1970), vocation affects the person’s life process and the satisfaction he gets of life directly. In this respect, person’s attitude towards his vocation and the value he attributes to it has a different importance.
Teachers’ professional behaviour of the values and altruistic investigation of self-esteem
Keywords: Eğitim, Eğitim Araştırmaları; İşletme